ANALISIS SET DAN PROPERTI FILM PENYALIN CAHAYA KARYA SUTRADARA WREGAS BHANUTEJA DALAM MENDUKUNG DRAMATIK - dewi, winda triana (Institut Seni Indonesia Padang Panjang, 2024)
ABSTRACTThe film Copying Light directed by Wregas Bhanuteja is a thriller drama genre that lasts 120 minutes and 73 scenes, tells the story of a student who is framed by her own friends so that she threatens to have her scholarship revoked. The research entitled